Determination of resistance capacities against thread failure and unbending of j-bolts used as roof fasteners - Sanidad, Jeremiah G.
New roof connection technique involves the use of j-bolts as roof fasteners and started to replace the typical connection such as wood nails and screws in the areas recently affected by typhoon which brought damage to the roof system of the structures. This study aims to measure the resistance capacity against thread failure and unbending of the J-bolts under the simulated loading condition. Tests includes the determination of capacity under static and dynamic loading. In addition to the capacity of the J-Bolt, this study also aims to measure the capacity of roof cover when subjected to connection with J-Bolts. Results shows that the capacity against thread failure had a significant increase compared to the wood nails, wood screws and metal screw; having a mean strength of 9.3 kN with standard deviation of 1.012. This type of failure is best represented by Weibull Distribution. Against unbending failure, the mean strength was recorded to be 2.829 kN with standard deviation of 0.231 . This mode of failure is best represented by Logistic Distribution. Two modes of failure were also examined for galvani zed iron sheets as roof covers namely: pull-thru failure (punching shear) and tearing failure. These failures both shows log normal distribution for their resistance capacities given the three typically used roof thickness.